A fogyatékossággal élő személyekkel kapcsolatos holisztikus megközelítések kialakulásának összefüggései - Szabó, Diána (Magyar Pedagógia, 2015)
A search for scholarship on the history of educating handicapped students in Hungary has produced only a few historically valuable comparative sociological studies. The aim of this paper is to present a comprehensive picture of the development of special education in Hungary and its present challenges. It also follows up on developmental trends in policy for the handicapped with a socio-economic focus. In my research, I sought an answer to the question: what kinds of original and unique developmental paths can be detected in the terminologies used in national special education? And what kinds of sociological changes have been imposed on it vis-à-vis the political aims and ideologies of the different eras? The sources of this research are the relevant national and international regulations and the international and national scholarly literature. In applying theoretical definitions, some terminological problems concealed behind the notions have been addressed, thus also raising questions not only for professional audiences, but also for legal and governmental ones. It is strategically important that the various policies should be streamlined, as this is a basic condition of cooperation between the various parties involved. The most important –indeed, urgent –policy problems regarding the handicapped are also outlined.